Covering layer structure and organic electroluminescent device

By adopting a screw ring structure and introducing alkyl groups into the cover layer material of the organic electroluminescent device, the problem of low glass transition temperature of the material is solved, and the luminescence effect with high efficiency and high color purity is achieved.

CN119562700APending Publication Date: 2025-03-04SHANGHAI QUADRISTAR ELECTRONIC TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411654090.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The glass transition temperature of existing organic electroluminescent devices is low, which affects the device life and luminous efficiency.

Method used

A helical ring structure is used as the main body, and alkyl groups are introduced on the outside of the helical ring structure to increase the glass transition temperature of the material while reducing the refractive index of the material.

Benefits of technology

The high glass transition temperature and low refractive index of the material are achieved, and the luminous efficiency and color purity of organic electroluminescent devices are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562700A_ABST
    Figure CN119562700A_ABST
Patent Text Reader

Abstract

The invention discloses a covering layer structure and an organic electroluminescent device, and relates to the technical field of organic electroluminescence, the covering layer structure comprises a first covering layer and a second covering layer located on the first covering layer, and the refractive index of the second covering layer is larger than that of the first covering layer; wherein the first covering layer comprises a compound shown as a formula I: # imgabs0 #, the compound of the first covering layer adopts a spiro ring as a main body structure, and the outer side of the spiro ring is connected with an alkyl group, so that the glass-transition temperature of the material can be kept at a relatively high level, and the material can have a low refractive index; when the first covering layer and the second covering layer with the high refractive index are used in a matched mode, the device can have excellent luminous efficiency and color purity at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of organic electroluminescence, and in particular to a covering layer structure and an organic electroluminescent device. Background Art

[0002] Organic Light-Emitting Diode (OLED). This light-emitting device has the characteristics of being thin, emitting light at high brightness at a low driving voltage, and being able to emit multi-color light by selecting light-emitting materials, so it has attracted much attention. Since the research by CW Tang and others from Kodak revealed that organic thin film elements can emit light at high brightness, a large number of OLED industry researchers have done a lot of research and promotion on its application, and its practical application has made great progress. Although the research on organic electroluminescence has been progressing very rapidly, there are still many problems that need to be solved, such as the external quantum efficiency (EQE) still needs to be improved.

[0003] For organic electroluminescent devices, the luminous quantum efficiency of the device is a comprehensive reflection of various factors and an important indicator for measuring the quality of the device. The current technology is to use amine derivatives with a specific structure with a high refractive index or use materials that meet specific parameter requirements as organic covering layer materials to improve light extraction efficiency and color purity, but the problem of taking into account both luminous efficiency and color purity has not yet been solved, especially in the case of preparing blue light emitting elements. In order to solve the problem of luminous efficiency and color purity, some researchers have found that when the covering layer uses a high refractive layer and a low refractive layer stacked, the problem of improving light extraction efficiency and color purity can be improved (CN111316461B), but in order to obtain a material with a lower refractive index, a large number of alkyl groups will be introduced into the molecular system, thereby bringing new problems, which reduces the glass transition temperature (Tg) of the material, which is not conducive to improving the life of the device. Summary of the invention

[0004] In order to solve the problem of lowering the glass transition temperature of the above-mentioned materials, the present application adopts a spirocyclic structure as the main body and introduces a strategy of an alkyl group on the outside of the spirocyclic main structure to ensure the high glass transition temperature of the material. Wherein the spirocyclic main structure is not conducive to the accumulation between molecules, which is conducive to reducing the refractive index of the material, and it is also a large π system in itself, so that the intermolecular force will not be reduced to too low, and at the same time, there is a large π conjugation in the system of the spirocyclic main structure, so that there is still a weak force between molecules, which is conducive to improving the glass transition temperature of the material, and these comprehensive factors enable the glass transition temperature of the material to be maintained at a high level.

[0005] In order to solve the above technical problems, this application provides the following technical solutions:

[0006] A first aspect of the present application provides a covering layer structure, comprising a first covering layer and a second covering layer located on the first covering layer, wherein the refractive index of the second covering layer is greater than the refractive index of the first covering layer; wherein the first covering layer comprises a compound as shown in Formula I: In Formula I: X is selected from a single bond, O, S; a, b, c and d are independently selected from 0, 1 or 2, and a+b+c+d≥2; R1 and R2 are independently selected from alkyl-substituted C6-C16 aryl, alkyl-substituted C3-C16 heteroaryl, cycloalkyl-substituted C6-C26 aryl, cycloalkyl-substituted C3-C26 heteroaryl, cycloalkyl-parallel C6-C16 aryl, cycloalkyl-parallel C3-C16 heteroaryl, trifluoromethyl-substituted C6-C R3 and R4, when they appear each time, are independently selected from C6-C16 aryl substituted with alkyl, C3-C16 heteroaryl substituted with alkyl, C6-C16 aryl substituted with cycloalkyl, C3-C16 heteroaryl substituted with cycloalkyl, trifluoromethyl, C1-C10 alkyl, C3-C10 cycloalkyl, C2-C10 heterocycloalkyl, or are bonded to adjacent atoms to form a ring; the substitution is mono- or poly-substitution.

[0007] A second aspect of the present application provides an organic electroluminescent device, comprising any of the aforementioned covering layer structures.

[0008] Compared with the prior art, this application has the following beneficial effects:

[0009] The covering layer structure of the present application includes a first covering layer with a low refractive index and a second covering layer with a high refractive index, wherein the compound of the first covering layer adopts a spirocyclic ring as the main structure and an alkyl group is connected to the outside thereof, which can not only keep the glass transition temperature of the material at a high level, but also make the material have a low refractive index. When the first covering layer is used in combination with the second covering layer with a high refractive index, the device can have both excellent luminous efficiency and color purity. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The following drawings describe in detail the exemplary embodiments disclosed in this application. The same reference numerals represent similar structures in several views of the drawings. Those skilled in the art will understand that these embodiments are non-limiting, exemplary embodiments, and the drawings are only used for the purpose of illustration and description, and are not intended to limit the scope of this application. Other embodiments may also accomplish the inventive intent in this application. It should be understood that the drawings are not drawn to scale. Among them:

[0011] Figure 1 This is a schematic diagram of the structure of the organic electroluminescent device prepared in Example 16 of the present application. DETAILED DESCRIPTION

[0012] The following description provides specific application scenarios and requirements of the present application, with the purpose of enabling those skilled in the art to make and use the content in the present application. It will be apparent to those skilled in the art that various local modifications to the disclosed embodiments are apparent, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the present application. Therefore, the present application is not limited to the embodiments shown, but to the widest scope consistent with the claims.

[0013] Although the existing cover layer material can improve the luminous efficiency and color purity of the device, the material has a large number of alkyl groups in the molecule, which makes the glass transition temperature of this type of material low, which is not conducive to improving the life of the device. Based on this, the present application creatively uses a spirocyclic structure as the main body, so that the alkyl group is connected to the outside of the spirocyclic structure, and the spirocyclic main structure can maintain the Tg of the material at a higher level. At the same time, the spirocyclic main structure is not conducive to the accumulation of material molecules, so the material can have a lower refractive index.

[0014] The following is an explanation of some terms involved in this application:

[0015] Aryl: If not otherwise specified, the aryl group may be a monocyclic aryl group or a polycyclic aryl group. In some embodiments, monocyclic aryl groups include, but are not limited to, phenyl, biphenyl, terphenyl, quaterphenyl, pentaphenyl, and the like. Polycyclic aryl groups include, but are not limited to, naphthyl, anthracenyl, phenanthrenyl, pyrenyl, peryl, fluorenyl, and the like. The fluorenyl group may be substituted, such as 9,9'-dimethylfluorenyl, 9,9'-dibenzofluorenyl, and the like. In addition, two of the substituents may be combined with each other to form a spiro ring structure, such as 9,9'-spirobifluorenyl, and the like. The above description of aryl groups may be used for aryl groups in aryloxy, arylthio, arylsulfonyl, arylphosphino, arylalkyl, arylalkylamine, arylalkenyl, alkylaryl, arylamine, and arylheteroarylamine.

[0016] Heteroaryl: Unless otherwise specified, heteroaryl refers to an aryl group containing one or more of B, N, O, P, S, Si and Se as heteroatoms. Heteroaryl includes, but is not limited to, pyridyl, pyrrolyl, pyrimidinyl, pyridazinyl, furanyl, thienyl, imidazolyl, pyrazolyl, oxazolyl, isoxazolyl, thiazolyl, isothiazolyl, triazolyl, oxadiazolyl, thiadiazolyl, dithiazolyl, tetrazolyl, pyranyl, thiopyranyl, pyrazinyl, azinyl, thiazinyl, dioxinyl, triazinyl, tetrazinyl, quinolyl, isoquinolyl, quinolyl, quinazolinyl, quinoxalinyl, naphthyridinyl, acridinyl, xanthenyl, phenanthridinyl, naphthyridinyl, triazaindenyl, indolyl, dihydroindole, indolizinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, pyrazinopy ... Pyrazinyl, benzothiazolyl, benzoxazolyl, benzimidazolyl, benzothienyl, benzofuranyl, dibenzothienyl, dibenzofuranyl, carbazolyl, benzocarbazolyl, dibenzocarbazolyl, indolocarbazolyl, indenocarbazolyl, phenazinyl, imidazopyridinyl, phenazinyl, phenanthridinyl, phenanthrolinyl, phenothiazinyl, imidazopyridinyl, imidazophenanthridinyl, benzimidazoquinazolinyl, benzimidazophenanthridinyl, spiro[fluorene-9,9'-xanthene], benzobinaphthyl, dinaphthofuranyl, naphthobenzofuranyl, dinaphthothienyl, naphthobenzothienyl, triphenylphosphine oxide, triphenylborane, etc. The above description of the heteroaryl group can be applied to the heteroaryl groups in the heteroarylamine group and the arylheteroarylamine group.

[0017] Alkyl: If not otherwise specified, the alkyl group may be linear or branched, including but not limited to methyl, ethyl, propyl, n-propyl, isopropyl, butyl, n-butyl, isobutyl, tert-butyl, sec-butyl, 1-methyl-butyl, 1-ethyl-butyl, pentyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, hexyl, n-hexyl, 1-methylpentyl, 2-methylpentyl, 4-methyl-2-pentyl, 3,3-dimethylbutyl, 2-ethylbutyl, heptyl, n-heptyl, 1-methylhexyl, cyclopentylmethyl, cyclohexylmethyl, octyl, n-octyl, tert-octyl, 1-methylheptyl, 2-ethylhexyl, 2-propylpentyl, n-nonyl, 2,2-dimethylheptyl, 1-ethyl-propyl, 1,1-dimethyl-propyl, isohexyl, 4-methylhexyl, 5-methylhexyl. The above description of the alkyl group can also be applied to the alkyl groups in the aralkyl group, alkylgermanyl group, aralkylamino group, alkylaryl group and alkylamino group.

[0018] Cycloalkyl: a cyclic saturated hydrocarbon group, such as cyclopropyl, cyclobutyl, cyclopentyl, 3-methylcyclopentyl, 2,3-dimethylcyclopentyl, cyclohexyl, 3-methylcyclohexyl, 4-methylcyclohexyl, 2,3-dimethylcyclohexyl, 3,4,5-trimethylcyclohexyl, 4-tert-butylcyclohexyl, cycloheptyl, cyclooctyl, etc.

[0019] Cycloalkyl-containing aryl groups: refers to aryl groups with cycloalkyl groups. For example, the cyclohexyl-phenyl ring structure, the cyclopentyl-phenyl ring structure, etc.

[0020] Cycloalkyl-coupled heteroaryl: refers to a heteroaryl group coupled with a cycloalkyl group, for example, a coupled ring structure of a cyclohexyl group and a pyridyl group, a coupled ring structure of a cyclopentyl group and a pyridyl group, etc.

[0021] Substitution: can be mono- or poly-substituted, where poly-substituted means di-, tri- or up to the maximum permissible poly-substituted.

[0022] The first aspect of the present application provides a covering layer structure, comprising a first covering layer, wherein the first covering layer comprises a compound as shown in Formula I: In formula I: X is selected from a single bond, O, S; a, b, c and d are independently selected from 0, 1 or 2, and a+b+c+d≥2, that is, the number of substituents on the spiro ring is not less than 2.

[0023] R1 and R2, when they appear each time, are independently selected from alkyl-substituted C6-C16 aryl (preferably C7-C16), alkyl-substituted C3-C16 heteroaryl, cycloalkyl-substituted C6-C26 aryl, cycloalkyl-substituted C3-C26 heteroaryl, cycloalkyl-parallel C6-C16 aryl, cycloalkyl-parallel C3-C16 heteroaryl, trifluoromethyl-substituted C6-C16 aryl (preferably C7-C16), trifluoromethyl-substituted C3-C16 heteroaryl.

[0024] In some preferred embodiments, R1 and R2 are independently selected from C1-C10 alkyl-substituted phenyl, C3-C10 cycloalkyl-substituted phenyl, C3-C10 cycloalkyl-substituted phenyl ring structure, trifluoromethyl-substituted phenyl.

[0025] In some preferred embodiments, each occurrence of R1 and R2 is independently selected from the following groups: Among them, R 1-2 is selected from C1-C5 alkyl, C5-C10 cycloalkyl, trifluoromethyl. n1-2 is selected from 1 or 2. * represents the connection site. Further preferably, the R 1-2 Selected from tert-butyl (tBu), trifluoromethyl, and adamantyl (Ad).

[0026] R3 and R4 are independently selected from alkyl-substituted C6-C16 aryl, alkyl-substituted C3-C16 heteroaryl, cycloalkyl-substituted C6-C16 aryl, cycloalkyl-substituted C3-C16 heteroaryl, trifluoromethyl, C1-C10 alkyl, C3-C10 cycloalkyl, C2-C10 heterocycloalkyl, or bonded to adjacent atoms to form a ring.

[0027] In some preferred embodiments, R3 and R4 are independently selected from phenyl substituted with C1-C10 alkyl, a ring structure of C3-C10 cycloalkyl and phenyl, trifluoromethyl, C1-C10 alkyl, C3-C10 cycloalkyl, or bonded to adjacent atoms to form a ring.

[0028] In some preferred embodiments, each occurrence of R3 and R4 is independently selected from the following groups: C1-C5 alkyl, C5-C10 cycloalkyl, trifluoromethyl, Or bonded with adjacent atoms to form a substituted or unsubstituted six-membered ring, for example, the R3 and R4 can be fused with their associated benzene ring to form Among them, R 3-4 is selected from C1 to C5 alkyl; n3-4 is selected from 1 or 2; * represents the connection site. Further preferably, the R 3-4 Selected from tert-butyl.

[0029] In some more preferred embodiments, the compound represented by formula I is selected from the following group:

[0030]

[0031]

[0032]

[0033] In the formula: X is selected from a single bond, O, S; b and d are independently selected from 1 or 2, and the number of substituents on the spiro ring is not less than 2;

[0034] R2 is selected from the following groups: * represents the ligation site.

[0035] R4 is selected from the following groups: Alternatively, it may be bonded to an adjacent atom to form a dimethyl-substituted six-membered ring; * represents the attachment site.

[0036] In some specific embodiments, the compound represented by formula I is selected from the following group:

[0037]

[0038] The cover layer structure of the present application further includes a second cover layer located on the first cover layer, and the refractive index of the second cover layer is greater than the refractive index of the first cover layer.

[0039] In some preferred embodiments, when refracting 460nm light, the difference between the refractive index of the second cover layer and the first cover layer is greater than 0.2. Further preferably, the refractive index of the second cover layer for 460nm light is greater than 1.9, for example, it can be 1.9, 1.95, 2.0, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, or a specific value in a sub-range composed of any of the above point values. More preferably, the refractive index of the second cover layer for 460nm light is 2.20. Further preferably, the refractive index of the first covering layer for 460 nm light is 1.4-1.7, for example, it can be 1.4, 1.45, 1.5, 1.51, 1.52, 1.53, 1.54, 1.55, 1.56, 1.57, 1.58, 1.59, 1.6, 1.61, 1.62, 1.63, 1.64, 1.65, 1.66, 1.67, 1.68, 1.69, 1.7, or a specific value in the sub-range composed of any point value above.

[0040] In some preferred embodiments, the second covering layer is formed of at least one of an inorganic compound and an organic compound, wherein the inorganic compound includes at least one of SiOx, SiNy, ZnS, ZnSe, ZrO, and TiO2, and x and y are independently selected from integers of 1 to 4. The organic compound includes at least one of an aromatic amine derivative, a carbazole derivative, a benzimidazole derivative, and a triazole derivative. Preferably, the organic compound includes at least one of the following compounds:

[0041]

[0042] The present application also provides an organic electroluminescent device, comprising any of the aforementioned covering layer structures.

[0043] In some preferred embodiments, the organic electroluminescent device further comprises: a cathode layer, and the covering layer structure is located on the cathode layer, wherein the first covering layer is close to the cathode layer.

[0044] In some embodiments, the organic electroluminescent device further comprises an anode layer disposed opposite to the cathode layer, and an organic layer is further stacked between the cathode layer and the anode layer. The organic layer may be a single-layer structure or a multilayer series structure in which two or more organic layers are laminated. The organic layer may include at least one organic functional layer selected from the group consisting of a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer, and each organic functional layer may be a single layer or a multilayer.

[0045] As an example, the structure of the organic light-emitting device may be selected from one of the following:

[0046] (1) The organic light-emitting device includes an anode, a hole injection layer, a first hole transport layer, a light-emitting layer, a first electron transport layer, a cathode, and a capping layer stacked in sequence, that is, anode / hole injection layer / first hole transport layer / light-emitting layer / first electron transport layer / cathode / capping layer. The device structure will be expressed in this simplified manner below.

[0047] (2) anode / hole injection layer / second hole transport layer / first hole transport layer / light-emitting layer / first electron transport layer / cathode / covering layer.

[0048] (3) anode / hole injection layer / second hole transport layer / first hole transport layer / light-emitting layer / first electron transport layer / second electron transport layer / cathode / covering layer.

[0049] (4) anode / hole injection layer / second hole transport layer / first hole transport layer / light-emitting layer / first electron transport layer / second electron transport layer / electron injection layer / cathode / covering layer.

[0050] (5) anode / hole injection layer / second hole transport layer / first hole transport layer / light-emitting layer / first electron transport layer / second electron transport layer / multilayer cathode / covering layer.

[0051] (6) anode / hole injection layer / first hole transport layer / first light-emitting layer / carrier generation layer / first hole transport layer / second light-emitting layer / first electron transport layer / cathode / covering layer.

[0052] (7) anode / hole injection layer / first hole transport layer / first light-emitting layer / carrier generation layer / first hole transport layer / second light-emitting layer / first electron transport layer / second electron transport layer / cathode / covering layer.

[0053] (8) anode / hole injection layer / second hole transport layer / first hole transport layer / first light-emitting layer / carrier generation layer / first hole transport layer / second light-emitting layer / first electron transport layer / cathode / covering layer.

[0054] (9) anode / hole injection layer / second hole transport layer / first hole transport layer / first light-emitting layer / carrier generation layer / first hole transport layer / second light-emitting layer / first electron transport layer / second electron transport layer / cathode / covering layer.

[0055] (10) Anode / hole injection layer / hole transport layer / electron blocking layer / light-emitting layer / electron transport layer / electron injection layer / cathode / covering layer.

[0056] (11) anode / hole injection layer / first hole transport layer / second hole transport layer / light-emitting layer / hole blocking layer / electron transport layer / cathode / covering layer.

[0057] (12) Anode / hole injection layer / hole transport layer / electron blocking layer / light-emitting layer / electron transport layer / cathode / covering layer.

[0058] (13) Anode / hole injection layer / hole transport layer / electron blocking layer / light-emitting layer / hole blocking layer / electron transport layer / cathode / covering layer.

[0059] (14) Anode / hole injection layer / hole transport layer / light-emitting layer / electron transport layer / electron injection layer / cathode / covering layer.

[0060] Some specific functional layers in the organic electroluminescent device will be described below.

[0061] Substrate:

[0062] The substrate is generally located below the anode, and the substrate may be made of plastic or glass, and may be rigid or bendable. The substrate is provided with a driving unit, which may drive the corresponding pixel to emit light.

[0063] anode:

[0064] The anode usually needs to meet requirements such as good conductivity, smooth surface, and no cracks. At the same time, there are certain requirements for the work function, mainly to be able to match the hole injection layer and exert the hole injection effect.

[0065] When the top emission mode (light emitting from the cathode side) is adopted, the anode adopts a metal compound with a work function of 4.2eV or more, such as indium tin oxide alloy, tin oxide, indium zinc oxide, gold, silver, platinum, copper, carbon nanotubes, carbon nanowires, graphene, etc. The thickness is 10nm to 200nm, preferably 10nm to 50nm. A reflective electrode is set under the anode (close to the substrate end). The reflective electrode is generally made of metal or metal alloy, such as silver metal, copper metal, aluminum metal, gold metal or alloys of these metals and other metals. The reflectivity of the reflective electrode is relatively high, and the reflectivity is required to be above 90%. The thickness is usually used at a thickness of 100nm to 500nm, preferably in the range of 80nm to 150nm.

[0066] The anode can be produced by forming an electrode material into a thin film by a method such as vapor deposition, sputtering, or coating.

[0067] Hole injection layer:

[0068] The thickness of the hole injection layer is generally 3nm to 30nm. The hole injection layer is a mixture of P-type materials and hole transport materials. The purpose of using P-type materials is to receive holes from the anode and transfer them to the hole transport material. The weight proportion of P-type materials in the hole injection layer is generally 0.5% to 10%. When the weight proportion is 0.5% to 3%, the absolute value of the difference between the lowest unoccupied molecular orbital (LUMO) energy level of the P-type material and the highest occupied molecular orbital (HOMO) energy level of the HTL material shall not be greater than 0.3eV. When the weight proportion is 3% to 5%, the absolute value of the difference between the lowest unoccupied molecular orbital (LUMO) energy level of the P-type material and the highest occupied molecular orbital (HOMO) energy level of the HTL material shall not be greater than 0.5eV. When the weight proportion is 5% to 10%, the absolute value of the difference between the lowest unoccupied molecular orbital (LUMO) energy level of the P-type material and the highest occupied molecular orbital (HOMO) energy level of the HTL material shall not be greater than 1eV.

[0069] The P-type material can be made of metal oxides, such as molybdenum oxide, vanadium oxide, tungsten oxide, etc.; it can also be made of organic matter, such as 4,4',4"-((1E,1'E,1"E)-cyclopropane-1,2,3-trimethylene tris(cyanoformylidene))tris(2,3,5,6-tetrafluorobenzyl) (PD1, CAS No.: 1224447-88-4), tetracyanoquinodimethane (TCNQ), 2,3,5,6-tetrafluoro-tetracyano-1,4-benzoquinodimethane (F4-TCNQ), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HAT-CN), and is not limited thereto. The hole transport material matched with the P-type material can be selected from the material of the second hole transport layer, and can be the same as the material of the second hole transport layer or different.

[0070] First hole transport layer:

[0071] The thickness of the first hole transport layer is generally 3nm to 500nm. When there is no second hole transport layer, the thickness of the first hole transport layer is generally 40nm to 150nm; when there is a second hole transport layer, the thickness of the first hole transport layer is generally 3nm to 500nm.

[0072] Second hole transport layer:

[0073] The thickness of the second hole transport layer is generally 5 nm to 150 nm, and an aromatic amine compound is often used, which may be an aromatic monoamine or an aromatic polyamine.

[0074] Electron blocking layer:

[0075] The electron blocking layer can have both hole transport and electron blocking functions. At the same time, the higher triplet excitation energy level of the electron blocking layer can lock the excitons generated in the light-emitting layer in the light-emitting layer, thereby improving the luminous efficiency of the device.

[0076] Luminous layer:

[0077] The material of the light-emitting layer generally includes a host material and a guest dopant material. The content of the host material is greater than that of the guest dopant material. Optionally, the mass percentage of the guest dopant material in the light-emitting layer is 1% to 20%.

[0078] The guest doping material as the luminescent material may include phosphorescent or fluorescent materials or thermally activated delayed fluorescent materials, and red light, green light, and blue light may be selected from the above three guest doping materials. For example, the guest doping material of the luminescent layer corresponding to the luminescent unit with a red luminescent color and the luminescent layer corresponding to the luminescent unit with a green luminescent color is a phosphorescent material, and the guest doping material of the luminescent layer corresponding to the luminescent unit with a blue luminescent color is a fluorescent material.

[0079] Or for example, the guest doping material of the light-emitting layer corresponding to the light-emitting unit with red light-emitting color and the light-emitting layer corresponding to the light-emitting unit with green light-emitting color is a phosphorescent material, and the guest doping material of the light-emitting layer corresponding to the light-emitting unit with blue light-emitting color is a phosphorescent material.

[0080] Or for example, the guest doping material of the light-emitting layer corresponding to the light-emitting unit with red light-emitting color and the light-emitting layer corresponding to the light-emitting unit with green light-emitting color is a thermally activated delayed fluorescent material, and the guest doping material of the light-emitting layer corresponding to the light-emitting unit with blue light-emitting color is a fluorescent material.

[0081] Or for example, the guest doping material of the light-emitting layer corresponding to the light-emitting unit with red light-emitting color and the light-emitting layer corresponding to the light-emitting unit with green light-emitting color is a thermally activated delayed fluorescent material, and the guest doping material of the light-emitting layer corresponding to the light-emitting unit with blue light-emitting color is a phosphorescent material.

[0082] As the light-emitting host material, one light-emitting host material or two light-emitting host materials may be selected.

[0083] Hole blocking layer:

[0084] In order to enhance the balance of hole and electron concentrations, a hole blocking layer is inserted to balance the carrier concentration and prevent exciton quenching. Generally, the hole blocking layer is located between the light-emitting layer and the electron transport layer. The hole blocking layer material must meet the conditions of strong stability, good film-forming properties, and a sufficiently high highest molecular occupied orbital.

[0085] First electron transport layer:

[0086] The thickness of the first electron transport layer can generally be 3nm to 40nm, 3nm to 10nm, 10nm to 20nm, 20nm to 30nm, 30nm to 40nm or 20nm to 40nm, etc. When there is no second electron transport layer, the thickness of the first electron transport layer is generally 20nm to 40nm, and when there is a second electron transport layer, the thickness of the first electron transport layer is generally 20nm to 30nm. The first electron transport layer is in direct contact with the light-emitting layer, so similar to the first hole transport layer, electronic changes will also occur during the electron transport process, resulting in increased molecular vibration and molecular deformation. The excitons of the light-emitting layer will also interact with the polarons of the electron transport material, which can easily produce active free radicals and destroy the electron transport material. The electron transport material can be a single compound or mixed with other metal compounds, such as Liq.

[0087] Second electron transport layer:

[0088] The thickness of the second electron transport layer is generally 10 nm to 40 nm, and the material of the second electron transport layer may include a mixture of an organic electron transport material and a metal compound, or a mixture of an organic electron transport material and a metal.

[0089] When the organic electron transport material is mixed with a metal compound material, for example, it is mixed with an alkali metal compound, an alkaline earth metal compound, a rare earth metal compound, and more specifically, it is mixed with a metal lithium compound, a metal calcium compound, a metal Mg compound, a metal samarium compound, a metal ytterbium compound, and more specifically, it is mixed with 8-hydroxyquinoline lithium, lithium fluoride, magnesium fluoride, ytterbium fluoride, calcium fluoride, etc. When mixed with a metal compound, the mass proportion of the organic electron transport material can be 20% to 80%, 20% to 40%, 40% to 60%, or 60% to 80%, etc.

[0090] When the organic electron transport material is mixed with a metal, for example, mixed with an alkali metal, an alkaline earth metal, or a rare earth metal, more specifically, mixed with lithium metal, magnesium metal, calcium metal, ytterbium metal, samarium metal, etc., when mixed with a metal, the mass proportion of the organic electron transport material can be 80% to 99%, 80% to 89%, 89% to 99%, 80% to 85%, 85% to 90%, 90% to 95%, or 95% to 99%, etc.

[0091] Electron injection layer:

[0092] The electron injection layer can reduce the barrier of electron injection from the cathode to the organic layer, improve the electron injection efficiency, and thus optimize the performance of the device. The material selection of the electron injection layer needs to consider its work function matching with the cathode material, and can be selected from alkali metals, alkaline earth metals, rare earth metals, or their inorganic substances or coordination compounds.

[0093] Charge generation layer:

[0094] When a single-layer light-emitting layer device is used, holes and electrons are injected from the anode and cathode respectively, and a charge generation layer is not required. When a double-layer or multi-layer light-emitting layer is used, a charge generation layer can be added between the light-emitting layers to achieve the effect of charge generation, injection and transmission. Generally, a P / N type two-layer material is used, wherein the P-type material is selected from the hole injection material mentioned above, and the N-type material is mixed with an organic electron transport material doped with a metal. The organic electron transport layer material is selected from the second electron transport layer mentioned above, and the metal is selected from alkali metals, alkaline earth metals, and rare earth metals, and more specifically, lithium metal, magnesium metal, calcium metal, ytterbium metal, samarium metal, etc. When the organic electron transport material is mixed with the metal, the mass proportion of the organic electron transport material can be 80% to 99%, 80% to 89%, 89% to 99%, 80% to 85%, 85% to 90%, 90% to 95%, or 95% to 99%, etc.

[0095] cathode:

[0096] The cathode requires a material with good electrical conductivity and good surface flatness. In order to improve the electron injection capability, a material with a small work function is usually selected. The cathode material can be a single-layer cathode, or a double-layer or multi-layer cathode, generally a metal or a metal alloy. For a single-layer cathode, silver, copper, aluminum, gold, or alloys of these metals with other metals, such as alloys with rare earth metals, alkali metals, and alkaline earth metals, can be used, which can be listed as magnesium-indium alloy, magnesium-aluminum alloy, aluminum-potassium alloy, aluminum-scandium-potassium alloy, magnesium-silver alloy, silver-ytterbium alloy, silver-samarium alloy, etc. If the cathode uses a double-layer metal, the cathode near the light-emitting layer can use alkali metals, alkaline earth metals, rare earth metals, etc., such as lithium, calcium, magnesium, ytterbium, etc., to increase the electron injection ability, and the cathode layer far from the light-emitting side is mainly used to improve the conductivity. Generally, silver, copper, aluminum, gold or alloys of these metals with other metals, such as alloys with rare earth metals, alkali metals, and alkaline earth metals can be used, which can be listed as magnesium-indium alloy, magnesium-aluminum alloy, aluminum-potassium alloy, aluminum-scandium-potassium alloy, magnesium-silver alloy, silver-ytterbium alloy, silver-samarium alloy, etc. The cathode can also be formed into a thin film by evaporation, sputtering, etc.

[0097] When light comes out from the anode side, the cathode is required to be light-proof, and a cathode with a thickness greater than 100nm can be evaporated. When light comes out from the cathode side, the cathode is required to be transparent, and the transmittance should be greater than 40% at this time, and the thickness should be 10nm to 20nm.

[0098] Cover:

[0099] The covering layer is formed on the cathode. A suitable covering layer material can improve the luminous efficiency of the device, and at the same time, the light extraction efficiency and viewing angle of red light, green light and blue light are more balanced.

[0100] In some preferred embodiments, two covering layers are used, and the total thickness can be 50nm to 90nm, for example: 50nm, 55nm, 57nm, 59nm, 62nm, 64nm, 67nm, 68nm, 70nm, 75nm, 77nm, 79nm, 80nm, 82nm, 85nm, 88nm, 90nm, etc.

[0101] In some preferred embodiments, the covering layer close to the cathode side uses a low refractive index covering layer, and the thickness can be 5nm to 40nm, for example: 5nm, 7nm, 10nm, 12nm, 15nm, 18nm, 20nm, 22nm, 25nm, 27nm, 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, etc.

[0102] In some preferred embodiments, the covering layer away from the cathode side adopts a high refractive index covering layer, and the thickness can be 35nm to 85nm, for example: 35nm, 40nm, 43nm, 45nm, 48nm, 50nm, 55nm, 57nm, 59nm, 62nm, 64nm, 67nm, 68nm, 70nm, 75nm, 77nm, 79nm, 80nm, 82nm, 85nm, etc.

[0103] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solution of the present application. Unless otherwise specified, the reagents and raw materials used can be purchased through commercial channels. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then according to general international standards, conventional methods and conditions, or according to the conditions recommended by the manufacturer, or selected according to the product specifications.

[0104] The starting materials and solvents of the following examples were purchased from Sinopharm, and some commonly used OLED intermediates and other products were purchased from domestic OLED intermediate manufacturers; various palladium catalysts and the like were purchased from Sigma Aldrich. HPLC data were measured using Shimadzu LC20AD high performance liquid phase analyzer; LC-MS (liquid chromatography-mass spectrometry) was tested on an H-class+SQD2 instrument from Waters Corporation.

[0105] Compound Preparation Example

[0106] Example 1

[0107] Preparation of compound 1

[0108]

[0109] Under argon atmosphere, add 47.4 g (100 mmol) of compound 1-A, 46.8 g (200 mmol) of compound 1-B, 787 mg (1 mmol%) of XPhos Pd G3, 50 mL (300 mmol) of 1.5 M potassium phosphate and 1000 mL (THF) of tetrahydrofuran to the reaction vessel, and stir under reflux for 12 hours. Cool to room temperature, add 800 mL of water, a large amount of solid precipitates, filter, wash the filter cake with water 3 times, and vacuum dry. The crude product is purified by silica gel column chromatography (eluent: ethyl acetate / hexane) to obtain 49.2 g of compound 1, with a yield of 71% and a HPLC purity of 99.9%. LC MS: M / Z 692.44 (M+).

[0110] Example 2 to Example 15

[0111] Referring to the preparation method of Example 1, compounds 2 to 15 shown in the following table were prepared.

[0112] Table 1 Reactants and products

[0113]

[0114]

[0115]

[0116] Tg test

[0117] The samples of compounds 1 to 15, CPL-1 and CPL-3 of the present application were tested using a differential scanning calorimeter DSC (TA Instruments, Inc., USA, model DSC25), and the Tg results shown in Table 2 were obtained.

[0118] Table 2 Tg test results

[0119] Compound Tg(℃) CPL-1 113 CPL-3 81 Compound 1 131 Compound 2 129 Compound 3 127 Compound 4 130 Compound 5 127 Compound 6 125 Compound 7 127 Compound 8 129 Compound 9 131 Compound 10 132 Compound 11 129 Compound 12 127 Compound 13 128 Compound 14 126 Compound 15 131

[0120] As can be seen from Table 2, the Tg of compounds CPL-1 and CPL-3 are relatively low, especially the Tg of compound CPL-3 is as low as 81°C. This is because the structural formula of compound CPL-3 contains a large number of alkyl groups, which leads to a large decrease in its Tg. Compounds 1 to 15 of the embodiments of the present application all use a spiro ring as the main structure and introduce an alkyl group on the outside, which can keep the Tg at a higher level. Therefore, the compounds of the present application have higher stability and are more suitable for organic electroluminescent devices.

[0121] Device Preparation Example

[0122] Example 16

[0123] refer to Figure 1 This embodiment provides a method for preparing an organic electroluminescent device, comprising the following steps:

[0124] (1) After the alkali-free glass 1 is ultrasonically cleaned in isopropyl alcohol for 15 minutes, it is treated with ultraviolet ozone in the atmosphere for 30 minutes, and then a 100 nm silver (Ag) film and a 10 nm ITO film (not distinguished in the figure) are sequentially formed on the alkali-free glass 1 using a radiometric method to form a reflective anode 2.

[0125] (2) The reflective anode 2 was subjected to a 10-minute ultraviolet ozone cleaning treatment, and a hole injection layer 3 (NPD and F4-TCNQ with a weight ratio of 97:3, 50 nm), a hole transport layer 4 (NPD, 80 nm), a blue light-emitting layer 5 (BH and BD with a weight ratio of 97:3, 20 nm), an electron transport layer 6 (Alq3, 35 nm) and an electron injection layer 7 (LiF, 1 nm) were sequentially deposited on the reflective anode 2 by vacuum evaporation, and then Mg and Ag (weight ratio of 10:1, 15 nm) were co-evaporated as a semi-transparent cathode 8.

[0126] (3) On the semi-transparent cathode 8, the low-refractive index compound 1 prepared in Example 1 is evaporated to form a first covering layer 91 with a thickness of 10 nm, and the high-refractive index compound CPL-2 is evaporated on the first covering layer 91 to form a second covering layer 92 with a thickness of 50 nm.

[0127] (4) In a glove box with a dry nitrogen atmosphere, an alkali-free glass sealing plate was packaged with an epoxy resin adhesive to produce an organic electroluminescent device.

[0128] Examples 17 to 30

[0129] The organic electroluminescent device was prepared in the same manner as in Example 16, except that when forming the first covering layer 91 , Compounds 2 to 15 prepared in the above examples were used instead of Compound 1.

[0130] Comparative Example 1

[0131] The only difference from Example 16 is that the material of the first covering layer 91 is the compound CPL-2, and the second covering layer 92 is not provided.

[0132] Comparative Example 2

[0133] The only difference from Embodiment 16 is that the second cover layer 92 is not provided.

[0134] Comparative Example 3

[0135] The only difference from Example 16 is that the material of the first covering layer 91 is the compound CPL-1, and the material of the second covering layer 92 is the compound CPL-2.

[0136] Comparative Example 4

[0137] The only difference from Example 16 is that the material of the first covering layer 91 is the compound CPL-3, and the material of the second covering layer 92 is the compound CPL-2.

[0138] The structural formula of the aforementioned compound is as follows:

[0139]

[0140] Device performance test

[0141] The refractive index of the cover layer was measured by ellipsometry (JA Woollam Co. Inc M-2000). At room temperature and pressure, a 10 mA / cm 2 The brightness and color purity of the device were tested using a luminescence luminance meter (CS1000, Konica Minolta Co., Ltd.) with a direct current of 1.5 % and a spectroradiometric sealed plate, and the luminous efficiency and color purity were obtained as shown in Table 3.

[0142] Table 3 Device performance test results

[0143]

[0144]

[0145] In Table 3, n1 refers to the refractive index of the first covering layer for light with a wavelength of 460nm, and n2 refers to the refractive index of the second covering layer for light with a wavelength of 460nm. According to the test results of Comparative Examples 1 to 2, when only a covering layer with a low refractive index is provided, the luminous efficiency of the device is low and the color purity is not high. Although Comparative Examples 3 to 4 simultaneously provide covering layers with a low refractive index and a high refractive index, which improves the luminous efficiency, the color purity is still not high. When the compounds of the embodiments of the present application are used to replace CPL-1 and CPL-3 and used in combination with high refractive index materials, the devices have both high luminous efficiency and high color purity.

[0146] In summary, by connecting an alkyl group to the outside of the spiro ring main structure, the present application can not only keep the glass transition temperature of the material at a high level, but also make the material have a very low refractive index. When it is used in combination with a material with a high refractive index, the device can have both excellent luminous efficiency and color purity. Therefore, the cover layer structure of the present application has good application prospects in the field of organic electroluminescent devices.

[0147] The above description of the embodiments is to facilitate those of ordinary skill in the art to understand and apply the present application. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to pay creative labor. Therefore, the present application is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the contents disclosed in the present application without departing from the scope and spirit of the present application are within the scope of the present application.

Claims

1. A covering layer structure, characterized in that: The method comprises a first covering layer and a second covering layer located on the first covering layer, wherein the refractive index of the second covering layer is greater than the refractive index of the first covering layer; wherein the first covering layer comprises a compound as shown in Formula I: In Formula I: X is selected from a single bond, O, and S; a, b, c and d are independently selected from 0, 1 or 2, and a+b+c+d≥2; R1 and R2 are independently selected from alkyl-substituted C6-C16 aryl, alkyl-substituted C3-C16 heteroaryl, cycloalkyl-substituted C6-C26 aryl, cycloalkyl-substituted C3-C26 heteroaryl, cycloalkyl-parallel C6-C16 aryl, cycloalkyl-parallel C3-C16 heteroaryl, trifluoromethyl-substituted C6-C16 aryl, trifluoromethyl-substituted C3-C16 heteroaryl; R3 and R4 are independently selected from alkyl-substituted C6-C16 aryl, alkyl-substituted C3-C16 heteroaryl, cycloalkyl-substituted C6-C16 aryl, cycloalkyl-substituted C3-C16 heteroaryl, trifluoromethyl, C1-C10 alkyl, C3-C10 cycloalkyl, C2-C10 heterocycloalkyl, or bonded to adjacent atoms to form a ring; The substitution is mono-substitution or poly-substitution.

2. The covering layer structure according to claim 1, characterized in that: The R1 and R2, when they appear each time, are independently selected from a phenyl group substituted with a C1-C10 alkyl group, a phenyl group substituted with a C3-C10 cycloalkyl group, a ring structure of a cycloalkyl group and a phenyl group, and a phenyl group substituted with a trifluoromethyl group; and / or, the R3 and R4, when they appear each time, are independently selected from a phenyl group substituted with a C1-C10 alkyl group, a ring structure of a cycloalkyl group and a phenyl group, a trifluoromethyl group, a C1-C10 alkyl group, a C3-C10 cycloalkyl group, or are bonded to adjacent atoms to form a ring.

3. The covering layer structure according to claim 1, characterized in that: Each occurrence of R1 and R2 is independently selected from the following groups: Among them, R 1-2 is selected from C1-C5 alkyl, C5-C10 cycloalkyl, trifluoromethyl; n1-2 is selected from 1 or 2; * represents the connection site; preferably, the R 1-2 Selected from tert-butyl, trifluoromethyl, and adamantyl.

4. The covering layer structure according to claim 1, characterized in that: The R3 and R4 are independently selected from the following groups when they appear each time: C1-C5 alkyl, C5-C10 cycloalkyl, trifluoromethyl, or bonded to adjacent atoms to form a substituted or unsubstituted six-membered ring; Among them, R 3-4 An alkyl group selected from C1 to C5; n3-4 is selected from 1 or 2; * represents a connection site; preferably, R 3-4 Selected from tert-butyl.

5. The covering layer structure according to claim 1, characterized in that: The compound represented by formula I is selected from the following group: In the formula: X is selected from a single bond, O, S; b and d are independently selected from 1 or 2, and the number of substituents on the spiro ring is not less than 2; R2 is selected from the following groups: * represents the junction site; R4 is selected from the following groups: The latter is bonded to the adjacent atom to form a dimethyl-substituted six-membered ring; * represents the ligation site.

6. The covering layer structure according to claim 5, characterized in that: The compound represented by formula I is selected from the following group:

7. The covering layer structure according to claim 1, characterized in that: When refracting 460nm light, the difference in refractive index between the second covering layer and the first covering layer is greater than 0.2; preferably, the refractive index of the second covering layer for 460nm light is greater than 1.9, and the refractive index of the first covering layer for 460nm light is 1.4-1.

7.

8. The covering layer structure according to claim 1, characterized in that: The second covering layer is formed of at least one of an inorganic compound and an organic compound, wherein the inorganic compound includes at least one of SiOx, SiNy, ZnS, ZnSe, ZrO, and TiO2, and x and y are independently selected from integers of 1 to 4; the organic compound includes at least one of an aromatic amine derivative, a carbazole derivative, a benzimidazole derivative, and a triazole derivative; preferably, the organic compound includes at least one of the following compounds:

9. An organic electroluminescent device, characterized in that: A covering layer structure comprising any one of claims 1 to 8.

10. The organic electroluminescent device according to claim 9, characterized in that: The organic electroluminescent device further comprises: a cathode layer, and the covering layer structure is located on the cathode layer, wherein the first covering layer is close to the cathode layer.

Citation Information

Patent Citations

  • Organic light-emitting elements

    CN111316461B